DEMOCRACY IN THE NETWORK SOCIETY: CITIZENSHIP AND POPULAR PARTICIPATION IN THE SMART CITIES CONTEXT - Dias, Jefferson Aparecido; de Oliveira, Diego Bianchi; Heinrich Ferrer, Walkiria Martinez [UNESP] (Instituto para o Desenvolvimento da Educacao, 2022)
Objective: This research aimed to investigate, in the light of theories of democracy, the new possibilities for exercising citizenship and strengthening democracy in the Network Society, as well as popular participation in political decisions in the context of smart cities. Methodology: The work adopted the inductive method, based on a literature review and observation of the phenomena. Results: It was possible to conclude that executing smart city projects does not only mean adhering to information and communication technologies, but also facilitating the connection and involvement of government and citizens, with the intention of co-creating and rebuilding urban communities. Contributions: Focusing on citizens and not simply on technologies, it is possible that ICTs and new technologies, including the IoT, improve the exercise of citizenship in current societies and, in particular, in smart cities.
DEMOCRACIA EN LA SOCIEDAD EN RED: CIUDADANÍA Y PARTICIPACIÓN POPULAR EN EL CONTEXTO DE LAS CIUDADES INTELIGENTES
DEMOCRACIA NA SOCIEDADE EM REDE: CIDADANIA E PARTICIPAÇÃO POPULAR NO CONTEXTO DAS SMART CITIES
Keywords: internet of things; network society; participatory democracy; smart cities